Performance analysis of static wireless body area network for different routing protocols - Vikas Shinde, Shilpa; Santosh S. Sonavane, Dr. (International Journal of Engineering and Technology, 2020)
Wireless body area network (WBAN) is a special type of wireless sensor network. It consists of sensors mounted on a human body to measure important body parameters. WBAN network uses different technologies such as IEEE 802.11, IEEE 802.15.4 and IEEE 802.15.6. In this paper, research outcomes focused on WBAN architecture design and performance analysis in a simulation environment for different routing protocols are done for IEEE 802.15.6. A comparative report is prepared for WBAN technology. Routing protocols are compared with each other based on energy consumption, throughput, and delay. For simulation purposes, a sensor network is designed by placing three sensors in a single hop star topology with a single central hub. The test run was successfully carried out to check the network configuration. A performance of three routing protocols for WBAN wireless technologies is investigated. These three routing protocols include AODV (Ad hoc On-Demand Distance Vector routing), DSDV (Destination Sequenced â€“Distance Vector routing) and DSR (Dynamic Source Routing). In three sets of simulation, the effect of various routing protocols on throughput, delay, and the energy consumption is calculated by increasing packet rate up to 2000 Kbps with an increment of 250 Kbps. Simulation results have shown that WBAN with AODV routing protocol is the most suitable to reduce power consumption and delay, and to increase throughput. Detailed analysis is discussed in the paper.Â Â